2013
DOI: 10.1111/srt.12094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of human skin in vivo: a comparative evaluation in 300 men and women

Abstract: The present study verifies the progressive decline of the skin mechanical properties with aging. However, the elastic ability of the skin to recover after stretching is more strongly affected by the aging process than the firmness of the skin. Further, the mechanical properties change differently in men and woman over lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 31 publications
9
123
1
1
Order By: Relevance
“…The analysis of the skin colour revealed a significant reduction of skin luminance ( L * value) with age, which is in concordance with previous studies that reported a diminution of this parameter with age on the face of female subjects [37, 38]. An increase in skin extensibility with age was also previously shown [18, 39], which might be explained by a loss of elastic fibres and changes in the extracellular matrix during skin ageing [39]. At the same time, aged skin showed reduced elastic recovery indicating that the skin is less able to regain its original state after deformation [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of the skin colour revealed a significant reduction of skin luminance ( L * value) with age, which is in concordance with previous studies that reported a diminution of this parameter with age on the face of female subjects [37, 38]. An increase in skin extensibility with age was also previously shown [18, 39], which might be explained by a loss of elastic fibres and changes in the extracellular matrix during skin ageing [39]. At the same time, aged skin showed reduced elastic recovery indicating that the skin is less able to regain its original state after deformation [37].…”
Section: Discussionsupporting
confidence: 91%
“…Functional parameters like skin surface pH, stratum corneum hydration (SCH) or transepidermal water loss (TEWL) are for instance applied as markers of the status and integrity of the skin barrier [14]. During ageing skin surface pH may increase, whereas TEWL decreases [15] and structural assessments revealed rougher human skin [16, 17] and decreased biological elasticity [18]. Age-dependent changes have also been demonstrated for skin colour [19].…”
Section: Introductionmentioning
confidence: 99%
“…With age, the amount and size of fibroblasts in the dermis decreases, as does the production of ECM by fibroblasts that remain in the skin [2][3][4][5][6]. This results in changes of the skin's structure and appearance, including a marked loss of skin elasticity and recoil, increased appearance of wrinkles and facial sagging skin, especially under the eyes [7][8][9][10][11]. External influences, such as UV radiation, which may cause appearance of sunspots and uneven skin color, can also cause reduced skin elasticity, wrinkling and sagging [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy of the epidermis, eyelid transparency in the dermis, loss of elasticity, eyelid wrinkles [23][24][25].…”
Section: Biological Clock's Alteringmentioning
confidence: 99%